2001
DOI: 10.1159/000050250
|View full text |Cite
|
Sign up to set email alerts
|

New Red Cell Parameters on the Sysmex XE-2100<sup>TM</sup> as Potential Markers of Functional Iron Deficiency

Abstract: Background:The ideal approach to monitor the haematological response of patients with anaemia associated with chronic renal failure during erythropoietin therapy is controversial. The reticulocyte haemoglobin content (CHr) and percentage hypochromic red cells (% Hypo) may be used as sensitive and specific indicators of functional iron deficiency in clinical situations with otherwise normal red cell indices. In the reticulocyte channel of a new blood cell counter using fluorescence flow cytometry, the Sysmex XE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 11 publications
0
30
1
Order By: Relevance
“…7, 2004 index, Ret-Y (RET-H e ), appears to be clinically equivalent to the CHr and offers an attractive potential tool for the diagnosis and monitoring of iron-restricted erythropoiesis. 3 Department of Biomedical Sciences, University "G. D'Annunzio", Chieti, Italy; 4 Centro Microcitemia Associazione Nazionale Microcitemia Italiana-ONLUS, Rome, Italy; 5 Human Genetic Laboratory, Galliera Hospital, Genoa, Italy; 6 Laboratorio di Patologia Genetica IRCCS Oasi Maria Santissima, Troina, Italy; * address correspondence to this author at: CSS-Mendel Institute, Viale Regina Margherita 261, 00198 Rome, Italy; fax 39-06-44160548, e-mail v.guida@css-mendel.it) ␣-Thalassemias (OMIM 141850 and 141800; GenBank accession no. NT037887) are recessively inherited hemoglobin disorders caused by loss of function of either one of the two duplicated ␣-globin genes (␣1 and ␣2), both located on chromosome 16p13.3 (1, 2 ).…”
Section: Potential Utility Of Ret-y In the Diagnosis Of Ironrestrictementioning
confidence: 99%
See 1 more Smart Citation
“…7, 2004 index, Ret-Y (RET-H e ), appears to be clinically equivalent to the CHr and offers an attractive potential tool for the diagnosis and monitoring of iron-restricted erythropoiesis. 3 Department of Biomedical Sciences, University "G. D'Annunzio", Chieti, Italy; 4 Centro Microcitemia Associazione Nazionale Microcitemia Italiana-ONLUS, Rome, Italy; 5 Human Genetic Laboratory, Galliera Hospital, Genoa, Italy; 6 Laboratorio di Patologia Genetica IRCCS Oasi Maria Santissima, Troina, Italy; * address correspondence to this author at: CSS-Mendel Institute, Viale Regina Margherita 261, 00198 Rome, Italy; fax 39-06-44160548, e-mail v.guida@css-mendel.it) ␣-Thalassemias (OMIM 141850 and 141800; GenBank accession no. NT037887) are recessively inherited hemoglobin disorders caused by loss of function of either one of the two duplicated ␣-globin genes (␣1 and ␣2), both located on chromosome 16p13.3 (1, 2 ).…”
Section: Potential Utility Of Ret-y In the Diagnosis Of Ironrestrictementioning
confidence: 99%
“…Although less frequent, at least 48 different nondeletional mutations (including point mutations and deletions/insertions of a few nucleotides), mostly located in the ␣2-globin gene, have also been reported as causative mutations of ␣ ϩ -thalassemia (3,4 ). At present, molecular identification of this type of nucleotide mutation is carried out by specific PCR amplification of the ␣2 or ␣1 gene, followed by methods that have only a limited rate of detection (60 -80%) and are technically demanding, such as single-strand conformation polymorphism (SSCP) analysis and denaturing gradient gel electrophoresis (5,6 ), or are costly, cumbersome, and time-consuming, such as direct sequencing and reverse dot-blot analysis (7,8 ).…”
Section: Potential Utility Of Ret-y In the Diagnosis Of Ironrestrictementioning
confidence: 99%
“…In addition, TfS is unreliable 12 , and ferritin values can be increased due to the presence of inflammatory cytokines. 13,14 Decreased erythropoiesis during ID, in combination with hemorrhage and a reduced lifespan of iron-deficient RBCs, can result in a complex form of iron deficiency anemia (IDA). 1 Erythrocyte morphology in advanced canine IDA is described as microcytic and hypochromic, evidenced by decreased MCV, MCHC, and MCH.…”
Section: Introductionmentioning
confidence: 99%
“…16,19,25,26 Analyzers manufactured by Sysmex use the mean value of the forward scattered light of mature RBCs and reticulocytes to calculate the RBC hemoglobin equivalent (RBC-He) and reticulocyte hemoglobin equivalent (RET-He). 13,14,22 Numerous studies in people have shown the diagnostic value of CHr in diagnosing FID, and a retrospective study established a RI for canine CHr 16 , suggesting that CHr might be a valuable screening tool for diagnosis of IDE in dogs. 16 Consistent with these results, experimentally induced ID in dogs was reflected earlier and more pronounced by a decline in CHr, and the response to therapy was detected earlier than by changes in RBC indices.…”
Section: Introductionmentioning
confidence: 99%
“…The index highly correlates with laboratory and endoscopic activity of the disease. All children underwent analysis of the blood stabilized with EDTA (calcium-sodium ethylenediaminetetraacete) using an automatic hematologic analyzer Sysmex 2000 I (Japan) to calculate parameters reflecting peripheral hemopoiesis (erythrocytes, erythrocyte indices, hemoglobin, leukocytes, platelets, platelet indices) [5]. Inflammatory markers and iron metabolism parameters (C-reactive protein (CRP), transferrin, iron) were studied in blood serum using a biochemical analyzer Unicell DxC 600 BD (USA).…”
Section: Methodsmentioning
confidence: 99%